Tree nut allergens. (August 2018) - Geiselhart, Sabine; Hoffmann-Sommergruber, Karin; Bublin, Merima
Highlights: Hazelnut, walnut, pecan, and cashew are potent sources of allergenic proteins. The majority of tree nut allergens belongs to the families of 2S albumins, vicilins, legumins, and nsLTPs. Bet v 1 homologues and profilins are associated with mild symptoms (pollen food syndrome). nsLTPs and seed storage proteins are related to severe reactions. High sequence identity within protein families is indicative for clinical cross-reactivity. Abstract: Tree nuts are considered as part of a healthy diet due to their high nutritional quality. However, they are also a potent source of allergenic proteins inducing IgE mediated hypersensitivity often causing serious, life-threatening reactions. The reported prevalence of tree nut allergy is up to 4.9% worldwide. The general term "tree nuts" comprises a number of nuts, seeds, and drupes, derived from trees from different botanical families. For hazelnut and walnut several allergens have been identified which are already partly applied in component resolved diagnosis, while for other tree nuts such as macadamia, coconut, and Brazil nut only individual allergens were identified and data on additional allergenic proteins are missing. This review summarizes the current knowledge on tree nut allergens and describes their physicochemical and immunological characterization and clinical relevance.